Maintenance Strategy of Cirebonese Language in Globalization Era - Setya Sukmayani, Nunik (Jurnal Edusci, 2023)
During the ruling of Syekh Syarief Hidayatullah at Keraton Pakungwati, Cirebonese language was used as the lingual franca in Cirebon. Cirebonese language was spoken and written in numerous activities and even in government affairs. However, the usage of Cirebonese language become less and less amidst the promotion of using Indonesian as a lingua franca in Indonesia. This was the result of preliminary observation in Cirebon. Although they promote the use of Indonesian language as the main language, Indonesian government also concerned with the maintenance of local languages. The government imposed the policy to include Cirebonese language as on subject at school from elementary schools to high schools. However, students still more often use Indonesian languages as their means of communication among their peers. Qualitative research methodology is applied in this research that focuses on the behavior of native speakers of Cirebonese language in finding the solution or strategy to maintain the local language in Cirebon.